Development patterns of an isolated oligo-mesophotic carbonate buildup, early Miocene, Yadana field, offshore Myanmar. (January 2020) - Teillet, Thomas; Fournier, François; Montaggioni, Lucien F.; BouDagher-Fadel, Marcelle; Borgomano, Jean; Braga, Juan C.; Villeneuve, Quentin; Hong, Fei
Abstract: The development history of an oligo-mesophotic, early Miocene, isolated carbonate system (>160 m in thickness), forming the uppermost part of the Oligo-Miocene Yadana buildup (northern Andaman Sea), has been evidenced from the integration of sedimentological core studies from 4 wells (cumulated core length: 343 m), well correlations, seismic interpretation and analysis of the ecological requirements of the main skeletal components. Three types of carbonate factory operated on the top of the platform, depending on water-depth, turbidity and nutrient level: (1) a scleractinian factory developing under mesophotic conditions during periods of high particulate organic matter supplies, (2) an echinodermal factory occupying dysphotic to aphotic area of the platform coevally with the scleractinian factory, (3) a large benthic foraminiferal-coralline algal factories prevailing under oligo-mesophotic and oligo-mesotrophic conditions. The limited lateral changes in facies between wells, together with the seismic expression of the Yadana buildup, suggest deposition on a flat-topped shelf. Carbonate production and accumulation on the Yadana platform was mainly controlled by light penetration, nutrient content and hydrodynamic conditions. Scleractinian-rich facies resulted from transport of coral pieces derived from mesophotic environments (mounds?) and deposited in deeper, low light, mud-rich environments in which lived abundant communities of suspension feeders such as ophiuroids. Changes in monsoonal intensity, terrestrial runoff from the Irrawaddy River, upwelling currents and internal waves activity during the early Miocene are likely responsible for significant variations in water turbidity and nutrient concentration in the Andaman Sea, thus promoting the development of an oligo-mesophotic, incipiently drowned platform. Highlights: An oligo-mesophotic isolated carbonate platform developed during the early Miocene. Coral-rich deposits are related to mesophotic carbonate production. Cycles of particulate organic matter influx are recorded in carbonate sedimentation. Internal waves, upwellings and terrigenous supplies controlled carbonate production.